Influence of Infant Massage Practice on Breastfeeding Among Mothers In Sarawak - Kim Geok, Chan; Saloma, Pawi; Shalin Wan Fei, Lee; Helmy, Hazmi; Chor Yau, Ooi; Zurraini, Arabi; Yoke Yong, Chen (FAKULTI PERUBATAN DAN SAINS KESIHATAN, UPM, 2021)
Introduction: Practice of infant massage by mothers has been reported previously to provide benefits such as nurturing touch, warmth and relaxation to infants and a more positive breastfeeding practice due to its stimulant for oxytocin release. This study aimed to determine the influence of infant massage by mothers on their breastfeeding practice in the local context. Methods: A quasi-experimental study was conducted among 310 mother-infant pairs who were recruited from five selected health centres within First Division of Sarawak. Intervention group participants (n=155) were taught to do infant-massage during the clinic session and instructed to practice 15 minutes twice daily throughout the two-months intervention period, while the control group (n=155) were not. Breastfeeding practice data were obtained using questionnaire from both groups pre-intervention at infants’ age one-month and post-intervention at age three-months. Results: Multinomial regression analysis showed that those in the intervention group were two times more likely than the control group for exclusive breastfeeding when compared to mothers who stopped breastfeeding (RR=2.022, 95% CI=1.007, 4.071; p-value=0.048). Similarly, mothers from the intervention group were two and half times more likely than control group for mixed feeding (RR=2.560, 95% CI=1.280, 5.121; p-value=0.008). Those who were housewives were nearly three times more likely than the private workers for exclusive breastfeeding (RR=2.734, 95% CI=1.246, 5.997; p-value=0.012). Conclusion: Infant massage influenced breastfeeding practice positively at infants’ age three-months, in particular, among mothers who were housewives. Healthcare providers should encourage infant massage practice by mothers as part of the maternal and child healthcare service.